Transformasi Ekologis dan Sosial di Amerika: Dampak Kebijakan Ekonomi terhadap Lingkungan dari Era Kolonial hingga Abad ke-21 M - Muna, Afifah Najdatul; Sianturi, Natalia Fronika; Simbolon, Lundu Wijaya; Nababan, Sarah Amelia; Karina, Karina; Sitorus, Oktavia; Nababan, Jeremia (Medan Resource Center, 2024)
This research explores ecological and social transformation in the Americas with a focus on the impact of economic policies on the environment from the colonial era to the present. Through historical analysis, this research examines how economic policies implemented by colonial powers, governments, and the private sector have influenced the continent's natural ecosystems and social structures. It found that intensive exploitation of natural resources, the introduction of unsustainable agricultural practices, and rapid industrialization have resulted in significant environmental degradation, including deforestation, loss of biodiversity, and pollution. In addition, economic policies have also triggered profound social changes, such as mass migration, urbanization, and changes in society's work structure. This study highlights the importance of a more sustainable and inclusive economic approach to reduce negative impacts on the environment and society. Thus, this research provides important insights for policy makers in designing economic strategies that are more harmonious with ecological sustainability and social welfare.